The Impact of Teacher’s Competence and Academic Supervision on the Effectiveness of Sekolah Penggerak - Samari, Samari; Kristiawan, Muhammad; Fitria, Happy (Graduate Program Magister Manajemen Pendidikan, 2023)
This study aims to examine whether there is a significant effect of teacher’s competence and academic supervision either partially or simultaneously on school effectiveness in Sekolah Penggerak (Driving School) Senior High School level in Palembang City. To achieve this goal, a quantitative approach is used. Data were collected using questionnaires, documentation, and observation. The results of the study show that teacher’s competence and academic supervision have a significant effect on school effectiveness both partially and simultaneously. The novelty of this research lies in the location and study that focuses on Sekolah Penggerak. This research contributes to teachers and the community in proving the magnitude of the influence of teacher’s competence and academic supervision on school effectiveness and helps socialize the Sekolah Penggerak program which is considered as a new government policy.